أسلوب المناقشة للمتوفقين في ترقية مهارة الكلام بقواعد اللغة العربية - Ahmad Mizan Rosyadi Abdul Jalil Manan (INAIFAS PRESS, 2019)
Speaking is a basic competance to success for learning language, especially Arabic. In the reality, most of students feel difficulty to make conversation, it is because of monopolized by educators showing up conversation skills and little opportunities for students to participate in learning activities and exersice. Participatory method is one of many methods in learning language that can make students more active in speaking. With quantitative expremental study by using observation, interview, and test, this research will be going to describe (1) participatory methods to improve students pronounciation on the right makhraj and (2) ways to improve vocabularies, Arabic grammar, motivation, and ability conversation.